(999) The Theory of Money and Monetary Equilibrium in Socialist Economy: An Study in Political Economy of Socialism (Part 1,2,3) نظرية المال والتوازن النقدي في الاقتصاد الاشتراكي : دراسة في الاقتصاد السياسي للاشتراكية (3 أجزاء) - Attia M.Soliman (2021)
The present work, on the basis of the Marxian "PoliticalEconomy", treats the problems of "The Theory of Money and Monetary Equilibrium". The author consider the analysis of these problems as a crucial and important in the development of theorizing the principles of the political economy of socialism. At the same time the author consider this analysis as a continuous study.